Development and characterization a novel leakage-proof form stable composite of graphitic carbon nitride and fatty alcohol for thermal energy storage. (30th November 2022) - Singh, P.; Sharma, R.K.; Goyal, R.; Hekimoğlu, G.; Sarı, A.; Rathore, Pushpendra Kumar Singh; Tyagi, V.V.
Abstract: The form-stabilization ability of the produced graphitic carbon nitride (g-C3 N4 ) for preventing the leakage of stearyl alcohol (SAOH) as promising organic phase change material (O-PCM) was investigated comprehensively. The SEM analysis showed that the g-C3 N4 had well defined pores which is capable to confine the molten SAOH in them. The FTIR and XRD confirm the chemical compatibility of g-C3 N4 and SAOH. The differential scanning calorimetry thermogram showed that the melting and freezing temperature of the FS-OPCMs including 70 wt% SAOH were 54.57 °C and 55.25 °C with respective high latent heats as 191 kJ/kg and 187 kJ/kg respectively. The thermal aging test for 1000 melt/freeze cycles confirmed that structure and thermal degradation durability are excellent. The thermal conductivity of developed FS-OPCM is enhanced by 122 %, which were resulted in about 50–54 % reduction in the charging/discharging time of FS-OPCM relative to the SAOH. The results exposed that the developed g-C3N4/SAOH (70 wt%) composite can be considered as potential solar energy storage material in different implementations such thermal cooling of photovoltaic panels, automotive and electronic units as well as solar residential water heating and passive solar space heating. Highlights: Synthesis of porous graphitic carbon nitride from a low cost urea Development of leakage proof form-stale PCM Enhanced thermal conductivity of stearyl alcohol Thermally and chemically durable FSOPCM